La metáfora del viaje en Un viaje de novios de Emilia Pardo Bazán - Kidakou, Antoine Bouba (Acta Hispanica, 2015)
Within the vast corpus of thenineteenth century Spanish narrative, EmiliaPardo Bazán’s Un viaje de novio, deserve adifferent consideration due to a particular styleadopted by the author and the consideration oftravel as an allegory of life. The author departs,hence fore, from the way how travel wasunderstood in the nineteenth century whenwriters based their travel writings or novels onthe scientific and educational aspects. PardoBazan explores the transcendental aspect oftravel fact and this paper studies the differenttechniques used by the writer to develop themetaphor of travel considering the geographicalmovement as an internal trip. The subjectiveand progressive transformation of the mainprotagonist, according to the itinerary of thetrip, is studied as that internal journey.